A Mathematical Modelling of Nitrogen Oxide Formation in a cng Spark Ignition Engine - Vladimir Hlavna; Daniela Zvarkova (Communications - Scientific letters of the University of Zilina, 1999)
Nitrogen oxides occupy aspecific position among gaseous harmful emissions produced by combustion engines. This position may externally appear as a coherence between energetic and ecological properties of the engine. The paper deals with a 3-D modelling of nitrogen oxides formation in a CNG ignition engine when the FLUENT programme is applied.